A voz do cantor eleva a classe: o Grupo de Acção Cultural Vozes na Luta nos anos da revolução, 1974-1976 - Hugo Castro; Ricardo Andrade; António Branco (Ler História, 2025)
GAC – Vozes na Luta, founded after the coup of 25 April 1974, was one of the most active artistic collectives in the first years of Portuguese democracy. It was characterized by the intense regularity of its performances throughout the country and by the publication of repertoire that narrated the revolutionary process. This article addresses, for the first time, José Mário Branco’s experiences during his exile in France and how these influenced the structuring of GAC, centralizing the various phases of the production and release of records, a peculiarity at the time. It also discusses the promotion of a “popular music” that combined the influence of traditional Portuguese music and agitprop songs. This article fills the gap in the scarce bibliography on the group and looks at its activities in its early years, from its creation as Colectivo de Acção Cultural to the release of LP Pois canté!!